Determinants Of Investment Interest From Young Accountants - Rahmawati Hanny Yustrianthe; Ronowati Tjandra (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
This study aims to determine the factors that influence the intention to invest either directly or indirectly. These factors include capital market education, investment knowledge and investment benefits. The population of this study were all students accounting in Yogyakarta who had attended capital market education and training. Samples were taken using the convenience sampling method, namely as many as 121 respondents. The data analysis technique used is path analysis assisted by PLS 3.0 software. The results of the study show that capital market education directly or indirectly has a positive and significant effect on investment intentions with investment knowledge and investment benefits as intervening variables.